2002
DOI: 10.1161/01.cir.0000036082.04708.83
|View full text |Cite
|
Sign up to set email alerts
|

Hypotension Caused by Extracorporeal Circulation

Abstract: Background-Cardiopulmonary bypass and hemodialysis often cause hypotension. We investigated a possible role of pump-induced platelet activation with consequent serotonin release. Methods and Results-In rats, a heparin-coated extracorporeal shunt was placed between the proximal part of a carotid artery and the distal part of a femoral artery. Autoperfusion did not affect platelets or hemodynamics. Pump perfusion, however, immediately elicited strong platelet aggregation, whereas aortic pressure rapidly fell to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 30 publications
(31 reference statements)
1
15
0
Order By: Relevance
“…Aggregating platelets normally release a number a substances including thromboxane A2, adenosine diphosphate and serotonin. In addition, serotonin released from aggregating platelets serves as a vasoconstrictor, but under normal conditions, and as aggregation subsides, reduced levels of serotonin can lead to vasodilation (119). It has been hypothesized that alteration in plasma serotonin level causes MH (MO or MA), and that platelet aggregation and heightened serotonin induce vasoconstriction causing reduction in blood flow and the neuronal manifestation of aura (14).…”
Section: Discussionmentioning
confidence: 99%
“…Aggregating platelets normally release a number a substances including thromboxane A2, adenosine diphosphate and serotonin. In addition, serotonin released from aggregating platelets serves as a vasoconstrictor, but under normal conditions, and as aggregation subsides, reduced levels of serotonin can lead to vasodilation (119). It has been hypothesized that alteration in plasma serotonin level causes MH (MO or MA), and that platelet aggregation and heightened serotonin induce vasoconstriction causing reduction in blood flow and the neuronal manifestation of aura (14).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is not entirely clear whether the HD dal -induced increase in PF4 results exclusively from platelet activation in the ECC or from the combination of platelet activation and release from endothelium-bound PF4. In rats, we demonstrated [12] that hemodynamic alterations during extracorporeal circulation were proportional to the amount of shear stress induced platelet aggregation and the subsequent rise in plasma serotonin levels. As all hemodynamic changes could be prevented by blockade of 5-hydroxytryptamine-2 receptors and by inhibition of NO formation, the observed fall in the BP was ascribed to serotonin-induced endothelial NO release.…”
Section: Discussionmentioning
confidence: 99%
“…In rats, we have previously shown that shear stress elicited platelet aggregation and subsequent serotonin release induce hypotension via endothelial NO release in a roller pump perfused extracorporeal circulation model [12]. Others [13] demonstrated a reduction in platelet activity at lower core temperatures in studies on cardiopulmonary bypass surgery.…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of NOS inhibition is plausible since current data suggest that NO mediates vasodilatation following CPB and rewarming, perhaps stimulated in part by release of proinflammatory cytokines [1, 2]. NO production is directly associated with temperature-dependent regulation of systemic vascular resistance during CPB: serum NO concentrations are significantly higher when CPB perfusion solution is tepid than when it is hypothermic [5].…”
Section: Discussionmentioning
confidence: 99%
“…Effects of CPB and the associated systemic hypothermia and rewarming, putatively mediated at least in part by cytokine release, routinely cause marked systemic vasodilatation, often resulting in profound (and rapidly developing) hypotension [1, 2]. Overproduction or excessive release of nitric oxide (NO) has been implicated in the development of this response [3, 4].…”
Section: Introductionmentioning
confidence: 99%